Uncovering the Grotesque in Fiction by Alice Munro and Gabrielle Roy - Hutchison, Lorna (Studies in Canadian Literature, 2008)
The importance of the grotesque aesthetic in Canadian literature of the last two centuries has outstripped literary theorists’ attempts to explain it as literary strategy. This contested term can usefully be defined as more than the use of a few scattered grotesque images: it is a narrative strategy that develops a pervasive sense of "hiddenness" – of unnameable dread and paradox. Central to this aesthetic, according to Philip Thomson and Susan Corey, are concepts of duality and deformity, both of which appear in many of the major works of Alice Munro, including The Love of a Good Woman (1998), but which are less evident in Gabrielle Roy’s mature work. In spite of the most disturbing elements in Roy’s The Tin Flute (1945), The Cashier (1954), and Enchanted Summer (1972), a comparison with Munro’s story "Fits" (1986) reveals that only Munro makes extensive use of the "true" grotesque.